Visitantes florais e eficácia de Xylocopa frontalis (Olivier, 1789) na polinização de Passiflora edulis f. flavicarpa Deg. (Passifloraceae) - Martarello, Natalia Seneda (Universidade Federal de São Carlos, 2016)
Pollination is an effective ecosystem service, responsible for increasing the quantity and quality of fruits and seeds formed. Due to the self-incompatibility of some species of agricultural interest, cross-pollination is required and the limiting of pollinating species such affects its production. The yellow passion fruit (Passiflora edulis f. flavicarpa.), a selfincompatible specie is dependent on cross-pollination to form fruit. Thus, the general aim of this study was to study the biology of pollination and reproduction in P. edulis f. flavicarpa, emphasizing the efficacy of pollinators for this specie. The specific aims were: 1) to evaluate the richness, visitation frequency and the behavior of visitors in Passiflora edulis f. flavicarpa flowers.; 2) to compare the efficacy in the formation of fruits and seeds of P. edulis f. flavicarpa through individual and two visits by Xylocopa frontalis with manual crosspollination and natural pollination and 3) assess whether there is pollen limitation through comparison between natural and manual cross-pollination. Visitors were observed during the flowering period, from January to April 2015, totaling 106 hours of observations. For fruiting testing and seed counts: 1) manual cross pollination (n = 37 flowers); 2) natural pollination (n = 52 flowers); 3) pollination by single visit of X. frontalis (n = 41 flowers) and 4) pollination by two visits of X. frontalis. Were identified bee species of Apis, Bombus, Centris, Epicharis, Eulaema, Melipona, Oxaea, Trigona and Xylocopa genera, Apidae, being also observed an individual belonging to Halictidae family. Insects belonging to other orders were also observed, including different species of butterflies (Lepidoptera), bugs (Hemiptera), flies (Diptera), beetles (Coleoptera) and the presence of family Trochilidae hummingbirds. The specie A. mellifera (thief behavior) and X. frontalis (predominantly pollinator behavior) were the most frequent in the plantation with 58.11% and 30.20% respectively of occurrence. Regarding pollination tests, we observed the formation of fruits in all the treatments. Flowers of manual cross-pollination obtained the highest fruiting rate when compared to other treatments. The fruiting rate through manual cross-pollination was significantly higher than that obtained in natural conditions (X2 = 12.676; degree of freedom = 1; p <0.05) indicating that there is pollen limitation in natural pollination. Regarding the number of seeds, an analysis of variance (ANOVA) indicated no significant difference between the mean number of seeds produced in different reviews pollination. Conclude that there is richness of floral visitors specie in the study area, and that between them, the main pollinator species are those with larger, mainly bees belonging to the genus Xylocopa. Larger fruiting rates obtained by manual cross-pollination treatment suggest that more than one visit is needed to promote greater production rate in passion fruit crops.
FLORAL VISITORS AND EFFICACY OF Xylocopa frontalis (Olivier, 1789) IN POLLINATION OF Passiflora edulis f. Flavicarpa Deg. (PASSIFLORACEAE)
Keywords: Maracujá-amarelo; Mamangava; Riqueza; Taxa de frutificação; Limitação polínica; Yellow passion fruit; Carpenter bee; Richness; Fruiting rate; Pollen limitation; CIENCIAS AGRARIAS